NEURO-PROTECTIVE EFFECTS OF CROCIN ON BRAIN AND CEREBELLUM TISSUES IN DIABETIC RATS - Altinoz, Eyup; Oner, Zulal; Elbe, Hulya; Vardi, Nigar (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Increase in free oxygen radicals and the disruption of defense system make the neurons and astrocytes more sensitive against oxidative damage. Materials and Methods: Rats were divided into three groups containing 10, rats in each group namely: control (C) group, Diabetes Mellitus (DM) group, and Diabetes Mellitus + crocin (DM+crocin) group. Tissue samples were processed by routine histological and biochemical procedures. The sections were stained with Hematoxylen-eosin. Malondialdehyde (MDA), glutathione (GSH), blood glucose, HbA1c levels and xanthine oxidase (XO) activities were assayed. Results: The histological appearence of the cerebrum and cerebellum were normal in the control group. DM group showed some histopathological changes including congestion, perivascular and perineuronal edema in cerebrum. In DM + crocin group, histopathological changes in cerebrum and cerebellum markedly reduced. MDA level and XO activities increased significantly in DM group (P<0.01), but decreased significantly in DM + crocin group when compared to DM group (P<0.01). Blood glucose concentrations increased significantly (p<0.01) in DM group), but decreased significantly in DM + crocin group when compared with DM group (p<0.05). Blood HbA1c levels were normal in control group. But there were significant differences between control and DM groups (p<0.01). On the other hand, blood HbA1c levels decreased in DM+crocin group when compared with the DM group, but it was not statistically significant (p > 0.05). Conclusion: Due to the fact that crocin has an antioxidant and anti-hyperglycemic effects, it can protect the brain and cerebellum tissue against the complications of oxidative stress.